Building women's economic empowerment - Suzi Nandera (International Trade Forum, 2016)
The adoption of the new Sustainable Development Goals (SDGs) in September 2015 marked a momentous year for the United Nations. They aim to transform lives in the 21st century and address such challenges as poverty, gender inequality and unemployment.